CAFFEINE USE AS A MODULATOR OF SLEEP QUALITY AND DURATION: IMPLICATIONS FOR HEALTH AND BEHAVIOUR - Jakub Piotrowski; Anna Jędrasiak; Patryk Heryć; Karolina Kananowicz; Zofia Laska; Marianna Latour; Zuzanna Kudlińska; Honorata Juniewicz; Julia Kosęda; Ryszard Łagowski (International Journal of Innovative Technologies in Social Science, 2026)
Caffeine is the most commonly consumed psychoactive substance worldwide, and it is a key factor modulating wakefulness. This makes its impact on sleep an important clinical and public health issue. The objective of this study was to provide a synthetic overview of current data on the effects of caffeine consumption on objective sleep parameters, including sleep latency, total sleep time, sleep efficiency, sleep architecture, and circadian rhythm regulation. These effects were taken to be contingent on dose, time of consumption, and population characteristics. A comprehensive literature review was conducted using the PubMed database, encompassing the period from 2000 to 2025. The focus of the review was on studies from the last decade or so, including randomized, observational, experimental, systematic review, and meta-analysis studies. The extant evidence unequivocally suggests that caffeine has a clear impact on the duration of sleep latency, the total duration of sleep, and the efficiency of sleep. It has been demonstrated that caffeine results in a reduction of slow-wave sleep (N3/SWS). These effects are dose- and time-dependent, and may persist even when caffeine is consumed up to six hours before bedtime. Polysomnography and electroencephalogram (EEG) studies have confirmed the presence of NREM sleep pressure disturbances and alterations in sleep organisation. The influence of individual variability, to a certain extent determined by polymorphisms of the ADORA2A and CYP1A2 genes, is of significance. Despite the extensive evidence base, there is still a lack of long-term prospective studies and projects that take genetic stratification into account. The results of the review indicate that caffeine should be considered an important modifiable risk factor for sleep disorders, and its rational use is a potentially simple but underutilized intervention to improve sleep health in the general population.